SPEAKING EXPRESSION: THE SOCIODRAMA TECHNIQUE IN ENHANCING STUDENTS' SPEAKING SKILL - Rahmiati; Iskandar Abdul Samad (University of Muhammadiyah Malang, 2022)
This research aimed to apply Sociodrama Technique in teaching speaking. The study's objective was to investigate whether there is a significant difference in speaking scores between learners treated by Sociodrama and those who were not. The methodology of this study was an experimental research method with a significance level of α=0.05. The samples of this study were 70 students in the 7th grade at one of the private junior high school in Lhokseumawe, Indonesia. These students were grouped into experimental and control groups, 35 students each. The instrument used was a test administrated in the form of pre-test and post-test. The data were analyzed using SPSS 20, the statistical package for social science. The data were considered normal and homogenous. From the t-test, the result showed that the critical area was higher than 2.00. The tcount value from the post-test between the Experimental and Control class is 2.54, which undoubtedly lies within the critical area. In conclusion, the sociodrama technique improved students' speaking ability.